2011
DOI: 10.3945/ajcn.110.001685
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of children’s eating behavior

Abstract: Parents have a high degree of control over the environments and experiences of their children. Food preferences are shaped by a combination of genetic and environmental factors. This article is a review of current data on effective determinants of children's eating habits. The development of children's food preferences involves a complex interplay of genetic, familial, and environmental factors. There is evidence of a strong genetic influence on appetite traits in children, but environment plays an important r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
244
3
26

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 278 publications
(288 citation statements)
references
References 57 publications
15
244
3
26
Order By: Relevance
“…Untuk perilaku enjoyment of food, umumnya mulai meningkat di usia 12 bulan dan terjadi penurunan di usia 5-6 tahun (16,23,25). Berdasarkan beberapa penelitian, perbedaan perilaku makan setiap anak dipengaruhi oleh faktor genetik, perilaku pemberian makan, pola asuh, perilaku makan orangtua, dan lingkungan obesogenik (26)(27)(28)(29)(30)(31).…”
Section: Bahasanunclassified
See 1 more Smart Citation
“…Untuk perilaku enjoyment of food, umumnya mulai meningkat di usia 12 bulan dan terjadi penurunan di usia 5-6 tahun (16,23,25). Berdasarkan beberapa penelitian, perbedaan perilaku makan setiap anak dipengaruhi oleh faktor genetik, perilaku pemberian makan, pola asuh, perilaku makan orangtua, dan lingkungan obesogenik (26)(27)(28)(29)(30)(31).…”
Section: Bahasanunclassified
“…Faktor genetik diketahui dapat memengaruhi perilaku makan pada anak, khususnya gen FTO (Fat mass obesity) yang berperan dalam mengontrol asupan makanan dan pilihan makanan (16,24,31). Selain itu, perilaku orangtua juga dapat memengaruhi perilaku makan anak yaitu melalui perilaku pemberian makan, dan perilaku makan orangtua (27,28,30,(35)(36)(37)(38).…”
Section: Bahasanunclassified
“…Factors affecting nutrition Children tend to have limited autonomy in their food intake and physical activity levels, with the majority of their choices determined by their parents and immediate family, and to a lesser extent their peers (71) . A study on Maltese 8-10-year-olds showed that children most liked eating pasta, pizza, chips, fruit and burgers, while their least liked foods were vegetables, meat, fish, soup and fruit (57) .…”
Section: The Micro-environmentmentioning
confidence: 99%
“…Studies that analyzed the formation of eating habits have shown that the parents exert a significant influence on the development of their children's behavior. [24][25][26] Skinner et al 27 analyzed children's food preferences and found that the mothers did not offer their children food that they themselves did not like, and that the children were less likely to reject the food that their mothers most enjoyed.…”
Section: Family's Attitudesmentioning
confidence: 99%